Analisis Minat dan Kreativitas Belajar Siswa dengan Menggunakan Aplikasi Google Classroom di SMKS Kesehatan Darussalam Lhokseumawe - Eka Utaminingsih (Jurnal Komputer, Informasi dan Teknologi, 2024)
The COVID-19 pandemic required schools to implement learning and training activities online. Google Classroom is one of the online learning platforms developed by Google and widely used during the pandemic. This research aimed to measure the level of creativity and interest of students in online ICT learning at SMKS Kesehatan Darussalam Lhokseumawe. A qualitative descriptive research design was employed, involving 28 students from SMKS Kesehatan Darussalam Lhokseumawe as participants. Research instruments included personal and online questionnaires consisting of 23 statements about interest and 15 questions about students' creativity in learning. The results showed that the majority of students had a high interest in online learning using Google Classroom, as reflected in the indicators of emotional happiness, attention, and interest, which achieved very good and good categories. Additionally, student engagement was also high. Analysis of pre-test and post-test creativity results also indicated an increase in students' creativity after following online learning. Therefore, online learning using Google Classroom has proven effective in increasing students' learning interest and creativity at SMKS Kesehatan Darussalam.